In-service teachers’ challenges to implementing an approach to critical thinking and critical reading in Chile - Leonardo Veliz (Universitas Ahmad Dahlan, 2021)
The present study reports on the challenges of implementing an approach to critical thinking and critical reading in English language teaching (ELT) in Chile. Participants in this research are in-service teachers of English enrolled in a Master’s course in Teaching English as a Foreign Language (TEFL) in Chile. In order to develop and construct a thorough understanding of the participants’ past and present academic literacy experiences, they were invited for one-to-one meetings (semi-structured interviews) where, rather than reminiscing about past literacy experiences, they were encouraged to engage in narratives about their experiences with and challenges of developing a socially critical awareness of literacy at university, and in their current teaching practices. Analysis of the participants’ accounts revealed, first and foremost, the pervasive presence of literacy practices that reflect and favor a strong culture of compliance over critical reflection, and, secondly, great concerns about the lack of systematic preparation in English teacher education (ETE) programs to develop and implement a more critical stance toward critical thinking and critical reading. The paper concludes by interrogating and challenging current university practices that, based on the participants’ views, seem to replicate a culture that reproduces both social and cultural inequalities.